Model Structural Equation Modeling untuk Analisis Standar Visi dan Bahasa pada Proses Knowledge Sharing Mahasiswa di Perguruan Tinggi - Vina Ayumi (Fakultas Teknik Universitas Muhammadiyah Bengkulu, 2025)
This study aims to analyze the factors influencing Tacit Knowledge Sharing (TKS) among university students using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS). The research model focuses on three main factors: Identification, Shared Language, and Shared Vision, which are believed to contribute to knowledge sharing in academic environments. Data were collected through self-administered questionnaires from 420 students, selected using the simple random sampling method. Hypothesis testing results indicate that Identification (β = 0.253, p < 0.05) and Shared Language (β = 0.326, p < 0.05) have a significant influence on TKS, while Shared Vision (β = 0.095, p = 0.057) has a weaker effect. These findings confirm that students’ sense of belonging within the academic community and shared language in communication play a crucial role in enhancing knowledge sharing, whereas a shared vision requires further strengthening strategies. This study provides implications for universities in developing policies that promote a knowledge-sharing culture to improve the quality of learning and academic collaboration.